PSYCHOMOTRICITY IN INCLUSIVE EDUCATION - Maria dos Santos Marcelino, Denise (Revista Gênero e Interdisciplinaridade, 2023)
The theme, psychomotricity, is very relevant mainly in the area of Early Childhood Education, a phase in which the child likes and is very interested in playing but can also be seen as a way to enrich the development of children with disabilities, therefore contributing to education inclusive. The education professional, not only the teacher, but everyone involved in this area must take advantage of and enrich the child’s taste for playing, seeking within this ludic field the opportunity for assertive inclusion. The objective of this work is to understand the contributions of psychomotricity, within Inclusive Education, aiming at development and working on the existing relationship between three aspects: Mind – Affection – Motor of all children. Psymotricity is a science of the body and mind, having as its starting point the psychological development of the child, that is, the elaboration of the “I” of the personality, of the body scheme, where the child learns to be aware of his own body and with that the possibility of expressing through this body. A poorly structured body schema results in a deficit in the subject-external world relationship, translating into: Perception: space-time structuring deficit; Motricity: clumsiness and incoordination in attitudes; Of the relationship with another: insecurity in this aspect, leading to the origin of affective disturbances, in addition to several other factors. Body movement is, without a doubt, therefore, a factor of great importance for the child. The process of appropriation, by the child, of his own body takes place in the context of relationships with others who support him, who offer him models, who encourage him, but who also limit, restrict and impede, coming against the idea of education with more equity.